Role and organization of a debt office - Borresen, Pal (UN New YorkUS, 2002)
Examines various models for the role, organization and location of a public debt office; the regulatory framework and institutional memory of debt management, involving the creation of procedure manuals for the inter-and intra- institutional tasks and information flows; and the degree of autonomy that a debt office can and should have.